Konstruksi Budaya Damai dalam Ikatan Persaudaraan Gandong Negeri Muslim-Kristen (Booi, Aboru, Kariu, Hualoy) di Maluku, Indonesia - Tubaka, Abdul Manaf (DIALEKTIKA, 2021)
This paper aims to describe how the construction of a peace culture in the brotherhood relations of gandong Booi, Aboru, Kariu, Hualoy (BAKH) through their involvement in building mosques and churches. This paper uses a qualitative method by relying on in-depth interviews through key informants selected intentionally (purposively), namely key actors in the community in the four BAKH countries and people involved in the BAKH organization. This paper shows that the worst humanitarian conflict in the history of the Moluccans did not necessarily destroy the traditional identity of the Moluccans, but instead emphasized the strong ties of adat and religion in the practice of Pela Gandong fraternity. This article emphasizes the importance of building a peace process through a cultural base that structurally influences the fundamental agent of local wisdom Pela Gandong. The construction of the peaceful cultural values of the Maluku people, thus requires the strengthening of the Pela Gandong traditional institutions in the midst of rapid social change.Key Word: Construction, Peace Culture, Gandong BAKH, Identity of culture and religion